A conceptual framework for Assessment-Informed Differentiation (AID) in the classroom. Issue 3 (3rd July 2021) - Eysink, Tessa H. S.; Schildkamp, Kim
ABSTRACT: Background : To enable all students to reach their full potential, teachers have to adapt their instruction to students' varying needs. In order to do this, teachers need to engage in activities associated with formative assessment, as well as those associated with differentiation. However, both of these types of activities are, in themselves, difficult for teachers to carry out. Furthermore, as both fields tend to use their own terminology, frameworks, and cycles of teacher activities, it can be even more difficult for teachers to navigate both. Although the notion of the strong relationship between formative assessment and differentiation is not new, we argue that a better understanding of the close relationship between the two is needed in the context of teacher education. Purpose: Our aim was to develop a conceptual framework which offers teachers and teacher educators a coherent set of teacher activities in which both formative assessment and differentiation are represented. Sources of evidence: International literature in the fields of formative assessment and differentiation was reviewed. Through this process, we sought to identify, describe and compare teacher activities regarded as crucial for formative assessment and for differentiation. The review was based on extant review studies and frameworks used in both fields and handbooks on both topics. Main argument: Our analysis demonstrated that both approaches have much in common, but differ substantially in terms of the emphasis placed on different activities and the depth of elaboration. As such, we argue that the approaches complement each other well and that it is feasible to present teachers with one coherent set of teacher activities in which both approaches are unified. We propose a conceptual framework for Assessment-Informed Differentiation (AID), which involves a continual cycle of in-depth activities related to preparing and providing differentiated instruction based on assessment data. Conclusion: Formative assessment and differentiation approaches need to be treated as an integrated set of activities in order to realise the full potential of all students. Further research should focus on the usability and effectiveness of the proposed cycle. The conceptual framework we propose could ultimately be used in many different teacher education settings internationally, forming a starting point for much-needed teacher professional development in this area.